Babushkas between Lesbian-Headed Families and the Russian State: Making an Intelligible Model of Extended Mothering - Zhabenko, Alisa (feminists@law, 2023)
This article focuses on a significant kinship character, babushka, the grandmother, in Russian lesbian-headed families. Based on an original empirical multi-method study, the research analyses the building of relationships with grandmothers in lesbian families in contemporary Russia. As the core element of Russian kinship – marriage – is missing from this kinship scene, blood relations between the biological mother, the maternal grandmother, and the child seem to become a central, although a highly complex element, in building supportive relationships in lesbian-headed families. Grandmothers from the non-biological mother’s side remain less visible in everyday negotiations and decision-making than biological grandmothers. The argument here states that blood relatedness becomes meaningful in situations where the grandmother’s role in lesbian-headed families is recognised and challenged in the officially anti-lesbian state context. Extended support mutually provided by grandmothers and their lesbian daughters creates an intelligible model of female-maintained family in current Russia, even when the legal landscape (i.e., the enforcement of the ‘anti-gay’ legislation in 2013) is not in the favour of such families. Consequently, babushkas become a “shield” between the state and the lesbian families as they provide a socially and culturally legit “traditional family” surface, required for survival in the state which promotes women’s reproduction as a core value in the society.